Man and superman. - Brady, Leo, 1917-; Waring, James D.; Lewis, Joseph H., 1907-2000; Shaw, Bernard, 1856-1950 (Penguin, 1966)
Olney Theatre, "Man and Superman," by George Bernard Shaw, directed by Leo Brady, settings and lighting by James D. Waring, costumes by Joseph Lewis.